2015
DOI: 10.4172/2157-7013.1000205
|View full text |Cite
|
Sign up to set email alerts
|

AQP7 Up-Regulation in the Skeletal Muscles of Mice with Diet Induced Obesity

Abstract: Aquaporin (AQP) 7 and AQP9 are membrane proteins and are the members of aquaglyceroporin which transports glycerol in addition to water molecule. Glycerol is a direct source of glycerol-3 phosphate for the synthesis of triglycerides. We thought that the expression of AQP7 and AQP9 would be altered in the skeletal myofibers in mice with diet-induced obesity (DIO) as compared with that of control chaw-fed mice. RNA and protein levels of AQP7 and AQP9 were studied in the quadriceps femoris muscles of mice with DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In this study, it was hypothesized that AQP7 and AQP9 mRNAs expression would be altered in the obese db/db mouse skeletal and cardiac muscles, since the neutral lipid, in which the triglyceride was a main substance, was increasing in these cells. As was observed in the skeletal muscles of obese ob/ob mice [ 33 ] and in diet induced obesity mice [ 32 ], upregulation of AQP7, but not AQP9 mRNAs in skeletal and cardiac muscles of db/db mice was revealed in this study. Increased AQP7 abundance was also described in skeletal muscle from obese men with type 2 diabetes [ 19 ].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In this study, it was hypothesized that AQP7 and AQP9 mRNAs expression would be altered in the obese db/db mouse skeletal and cardiac muscles, since the neutral lipid, in which the triglyceride was a main substance, was increasing in these cells. As was observed in the skeletal muscles of obese ob/ob mice [ 33 ] and in diet induced obesity mice [ 32 ], upregulation of AQP7, but not AQP9 mRNAs in skeletal and cardiac muscles of db/db mice was revealed in this study. Increased AQP7 abundance was also described in skeletal muscle from obese men with type 2 diabetes [ 19 ].…”
supporting
confidence: 80%
“…An increase in lipid content has been reported in the skeletal muscle cells of obese animals [ 14 , 23 , 28 , 32 , 33 ]. The increased lipid content, such as triglycerides, in the skeletal and / or cardiac muscle cells is synthesized with glycerol and fatty acids in the muscle cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AQPs are intrinsic membrane proteins that form channels in epithelial and endothelial cells [22]. AQP7 apparently regulates the efflux of lipolysis-derived glycerol from adipocytes, which are essential in the maintenance of normal adiposity [22].…”
Section: Discussionmentioning
confidence: 99%
“…AQPs are intrinsic membrane proteins that form channels in epithelial and endothelial cells [22]. AQP7 apparently regulates the efflux of lipolysis-derived glycerol from adipocytes, which are essential in the maintenance of normal adiposity [22]. A previous study had shown that AQP7 is up-regulated by fasting, low insulin and PPARα and altered expression may be related to lipid metabolism disorders [23].…”
Section: Discussionmentioning
confidence: 99%